Does team leader gender matter? A Bayesian reconciliation of leadership and patient care during trauma resuscitations. Issue 1 (4th January 2021) - Rosenman, Elizabeth D.; Misisco, Anthony; Olenick, Jeffrey; Brolliar, Sarah M.; Chipman, Anne K.; Vrablik, Marie C.; Chao, Georgia T.; Kozlowski, Steve W. J.; Grand, James A.; Fernandez, Rosemarie
Abstract: Objective: Team leadership facilitates teamwork and is important to patient care. It is unknown whether physician gender‐based differences in team leadership exist. The objective of this study was to assess and compare team leadership and patient care in trauma resuscitations led by male and female physicians. Methods: We performed a secondary analysis of data from a larger randomized controlled trial using video recordings of emergency department trauma resuscitations at a Level 1 trauma center from April 2016 to December 2017. Subjects included emergency medicine and surgery residents functioning as trauma team leaders. Eligible resuscitations included adult patients meeting institutional trauma activation criteria. Two video‐recorded observations for each participant were coded for team leadership quality and patient care by 2 sets of raters. Raters were balanced with regard to gender and were blinded to study hypotheses. We used Bayesian regression to determine whether our data supported gender‐based advantages in team leadership. Results: A total of 60 participants and 120 video recorded observations were included. The modal relationship between gender and team leadership (β = 0.94, 95% highest density interval [HDI], ‐.68 to 2.52) and gender and patient care (β = 2.42, 95% HDI, ‐2.03 to 6.78) revealed a weak positive effect for female leaders on both outcomes. Gender‐based advantages to team leadership and clinical care were not conclusively supported or refuted, with the exception of rejecting a strong male advantage to team leadership. Conclusions: We prospectively measured team leadership and clinical care during patient care. Our findings do not support differences in trauma resuscitation team leadership or clinical care based on the gender of the team leader.